Interpersonal relationships in the nursing care of people with type 2 diabetes - Maria de Jesus Nascimento de Aquino; Francisca Diana da Silva Negreiros; Ana Célia Caetano de Souza; José Wicto Pereira Borges; Tatiana Rebouças Moreira; Thereza aria Magalhães Moreira (Universidade Federal do Estado do Rio de Janeiro, 2023)
Objective: to analyze the effectiveness of the interpersonal relationship in nursing care and its relationship with general self- care and foot care in people with type 2 diabetes. Method: this cross-sectional, analytical study was conducted at a University Hospital with 150 people with type 2 diabetes who answered the  Interpersonal Relationship in Nursing Care Questionnaire, a questionnaire on self-care activities with diabetes, and a questionnaire to assess adherence to feet self-care. Results: the results showed that the effectiveness of the interpersonal relationship in care ranged from moderate to high. The questionnaire scores were significant with nephropathy comorbidities, cerebrovascular accident, diet adherence, and receiving foot care guidance. Conclusion: interpersonal relationships in effective care can strengthen bonding, trust, and verbalization of feelings, improving diabetes education and adherence to self-care behaviors.